Formação de professores alfabetizadores: desafios da docência - Wasilewski, Cassiana da Silva (2020)
The objective of this research is to present the training of the current literacy teachers in the initial grades of three schools of the São Paulo Municipal School, in the West region, and to research some aspects of this formation that are reflected in the practice, listing the essential knowledge that the literacy teacher presents by through the elaboration of a profile about the literacy teachers, interviewees, regents of the 1st and / or 2nd years of the Elementary School at PMSP at DRE Butantã. We made a study about the teaching methods of reading and writing, then we tried to identify some aspects of this initial formation that underlie their practices in PMSP. Literacy teachers who join the Municipal Network go through a legal process when taking up their public office or accepting a work contract. When entering these professionals face several difficulties, especially in literacy classes. An initial education that underpins the learning of reading and writing processes is an important step to ensure the training of literacy teachers. Profiling literacy professionals can provide an understanding of the real needs surrounding the literacy process in order to understand which aspects of their initial education (faculty) effectively contribute to pedagogical action in children's literacy. We will adopt a theoretical framework focused on research on literacy, literacy methods and teacher education from a critical perspective and from the point of view of written language psychogenesis and social interactions. The methodology will be qualitative with documentary analysis, specific bibliographic reading and interviews, following a theoretical framework with Braslavsky (1971), Feldmann (2017), Ferreiro (1990 e 2006), Goodman (1995), Kato (1988), Noffs (2018), Soares (2004 e 2018), among others. Expected outcomes are associated with gaps in early education and child literacy outcomes